HUBUNGAN PARTISIPASI ORANG TUA DALAM PENDIDIKAN DENGAN PRESTASI AKADEMIK SISWA SEKOLAH DASAR - Rheza Safitri, Yunita Amilia Aini Rohmah, Nur Atikah, Sekar Dwi Ardianti, Erik Aditia Ismaya (CV. ADIBA AISHA AMIRA, 2024)
This research is motivated by the participation of parents in supporting students in academic and non-academic achievements. This research uses a correlational method that looks for the relationship between parental participation in education and student academic achievement. The sample for this research was 13 parents of grade 5 students in one of the elementary schools in Jepara City. The research instrument consists of a questionnaire and documentation. The research results show that there is a relationship between parental involvement in education and elementary school students' learning achievement of 0.003. The figures obtained show that there is a positive relationship between parental participation in education and student academic achievement, the relationship category is at a low level. This means that parental involvement in education has a relationship with student achievement, but there is still a contribution from other factors which have a closer relationship with student achievement, but were not examined in this research.